IMPLICIT AND EXPLICIT ASSESSMENT OF ATTITUDE TO HEALTH - Dudchenko, Z.F.; Nikiforov, G.S.; Rodionova, Е.А.; Dominyak, V.I.; Fontanetskaya, E.G. (Modern Psychology, 2019)
To study the characteristics implicit and explicit attitude to health, 101 respondents were examined, with an average age of 24 years and work experience of about 3 years. The following were measured: implicit assessment of attitude to health (computer technique "Mental map of health"), explicit assessment of attitude to health (method "Type of attitude to disease"), health status (The world health organization quality of life WHOQOL -brief). Respondents who have a positive implicit assessment of attitudes to health and disease are characterized by higher health indicators. Respondents who have a negative implicit assessment of the relationship to health and disease are characterized by a disturbing attitude to health. Respondents with different implicit health assessments have different health conditions and differences in explicit health assessments.
Keywords: attitude to health; implicit and explicit attitude to healt